Estimating retirement behavior with special early retirement offers - Matias Eklöf; Daniel Hallberg (Uppsala University, Department of Economics, 2006)
We model retirement behavior in Sweden during the 1990ies with focus on voluntary early retirement where there is an option for buy-outs. An employer can offer the employees generous pension programs if the employee agrees on early retirement. Earlier studies have neglected such offers, but in doing so, estimates of the individuals responses to financial incentives in a retirement decision are likely to be biased upward. We propose an estimation strategy where the retirement decision and the accesses to early retirement pension offers are estimated in a simultaneous equation system, yielding unbiased estimates of the model parameters. We apply the model using detailed Swedish register data. Our results indicate that the marginal effects in retirement probability w.r.t. a change in financial incentives is less pronounced if early retirement pensions are accounted for. Further, we illustrate that the early retirement probabilities would decrease by 10-30 percent if early retirement pension offers were absent.
urn:nbn:se:uu:diva-83087
Keywords: J14; J21; 330; Retirement; early retirement pension; golden handshakes; occupational pension; demand for old workers; Altersgrenze; Ältere Arbeitskräfte; Altersvorsorge; Abfindung; Betriebliche Altersversorgung; Schweden